2017
DOI: 10.1186/s40249-017-0323-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of diarrhoea and risk factors among children under five years old in Mbour, Senegal: a cross-sectional study

Abstract: BackgroundDiarrhoeal diseases remain an important cause of mortality and morbidity among children, particularly in low- and middle-income countries. In Senegal, diarrhoea is responsible for 15% of all deaths in children under the age of five and is the third leading cause of childhood deaths. For targeted planning and implementation of prevention strategies, a context-specific understanding of the determinants of diarrhoeal diseases is needed. The aim of this study was to identify risk factors of diarrhoeal di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
75
6
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(125 citation statements)
references
References 29 publications
(21 reference statements)
24
75
6
4
Order By: Relevance
“…Similarly, the result of this study noted lower prevalence of childhood illness compared to some studies conducted elsewhere (9,11,13,16). There could be several explanations for the differences in prevalence of the illnesses with this findings and across literatures.…”
Section: Discussionsupporting
confidence: 78%
“…Similarly, the result of this study noted lower prevalence of childhood illness compared to some studies conducted elsewhere (9,11,13,16). There could be several explanations for the differences in prevalence of the illnesses with this findings and across literatures.…”
Section: Discussionsupporting
confidence: 78%
“…In the multivariate analyses (Table 2) water, versus households utilizing reverse osmosis water, in Thi-Qar [37]. A community crosssectional study in Mbour, Senegal by Thiam et al [38] observed children living in better-off families were less likely to have diarrhoea compared to their lower income counterparts. Our results are in line with several household studies on diarrheic children that have demonstrated that the wealth status of the family is correlated with better access to household amenities, including those related to better hygiene and environmental health, which likely reduce the risk of diarrhoea [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…These results are in agreement with what was reported from studies conducted in neighboring countries such as Turkey [40], Iran [33] and Jordan [27], where children belonging to mothers with a higher education level (university or diploma) were less likely to have diarrhoea compared to those whose mothers had a lower level education (primary or secondary) or were illiterate. This finding might indicate that those mothers who have a higher education level are attaining more awareness on good child feeding practices, hygiene behaviors and safe handling of water which in turn are important factors for reducing the risks associated with childhood diarrhoea [21,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. In addition to mothers' education level, the present study observed that the reported occurrence of diarrhoea is likely to be less in children belonging to mothers aged >25 years compared to mothers aged ≤25 years.…”
Section: Discussionmentioning
confidence: 99%
“…Diarrhea is a major public health problem worldwide, being one of the major causes of infant morbidity and mortality, representing the second leading cause of death in children under five years of age [59]. About a third of children living in developing countries, where unfavorable hygienic-sanitary conditions facilitate the spread of pathogens, are affected by enteric infections with or without diarrheal events [60].…”
Section: Sc Against Cumulative Cch Contractions In Isolated Rat Jejunmentioning
confidence: 99%